A novel algicidal properties of fermentation products from Pseudomonas sp. Ps3 strain on the toxic red tide dinoflagellate species - Zheng, Luwei; Lin, Hong; Balaji-Prasath, Barathan; Su, Yuping; Wang, Ying; Zheng, Yi; Yu, Guanglang (Frontiers in Microbiology, 2023)
The safety of China's offshore fisheries and the world's marine fisheries are threatened by red tides of Gymnodinium catenatum and Karenia mikimotoi. Effective control of dinoflagellate red tides has become an urgent problem to solve. Here we address the effects of algicidal bacteria on the red tides species G. catenatum and k. mikimotoi in an indoor enclosure experiment in which high-efficiency marine alginolytic bacteria were isolated to carry out molecular biological identification of algicidal bacteria. When combining morphological, physiological, biochemical, and sequencing results, strain Ps3 was identified as Pseudomonas sp. This investigation demonstrated that with exposure to the algae-lysis experiment, the Ps3 strain has the best algae-lysis effect, with G. catenatum and K. mikimotoi reaching 83.0% and 78.3%. The inhibitory effect of the sterile fermentation broth experiment on the two red tide algae was positively correlated with the dosage. When the dosage volume ratio (v/V) was 2%, the 48h algae lysis rates of Ps3 bacterial fermentation broth to G. catenatum and k. mikimotoi were 95.2% and 86.7%. In all cases, changes in cellular morphology were observed, suggesting that the algaecide may be an effective and rapid approach to mitigate dinoflagellate blooms. Gas chromatography-mass spectrometry (GC-MS) was used to analyze the structure of the algolytic active substances. In the ethyl acetate phase of Ps3 fermentation broth, the cyclic (leucine-leucine) dipeptide was the most abundant. This study provides a theoretical basis for the study of red tide prevention and control.